Language and Sustainability, Linguistic Sustainability: Between Economization and Simulative Democracy? - Goranka Rocco (Linguistica)
The study is intended as a contribution to linguistic reflection on the desideratum of sustainability in relation to the use of language and to discourses on language. Starting from the question of how the concept of linguistic sustainability is used in different languages and linguistic approaches, it discusses the results of early research in the field of ecolinguistics and the ecology of language, as well as the competing and partly overlapping concepts of (linguistic) diversity and vitality. It then explores the question of how sustainability, hegemonic aspirations and monolingual or multilingual language habitus relate to each other, especially in an age of increasing economization of knowledge and growing ranking pressure on educational and research institutions: Is the goal of linguistic sustainability and the preservation of linguistic-cultural diversity seriously pursued and perceived as achievable, or are the corresponding key terms (multilingualism, diversity) primarily part of a basically inconsequential “post-materialist” discourses? The considerations lead to a reflection on the possibilities and limits of linguistic sustainability with regard to the progressive economization of knowledge and science, which influence language use, and on the other hand with regard to the gap between real developments, which seem to privilege one or at best a few languages, and the official narratives on the promotion of multilingualism. This gap is interpreted in the context of the hypothesis of structural or systemic social unsustainability (Blühdorn 2020) and particularly in line with Blühdorn’s concept of ‘Simulative Democracy’ (2013).